THE INTEGRATION OF RELIGIOUS MODERATION INTO THE CURRICULUM AT THE HARISUL KHAIRAAT BUMI HIJRAH ISLAMIC BOARDING SCHOOL IN TIDORE - Bayanuddin Sudin; Sahjad M. Aksan; Agus; Buyung Tawary (STAI Nusantara Kota Banda Aceh, 2026)
This study aims to analyze the internalization of religious moderation within the learning curriculum at Harisul Khairaat Bumi Hijrah Islamic Boarding School in Tidore. Religious moderation refers to religious perspectives, attitudes, and practices that emphasize the principles of balance, justice, tolerance, and respect for diversity. In the context of Islamic boarding school education, the internalization of religious moderation is essential for developing students who possess a comprehensive and moderate understanding of religion and are capable of living harmoniously within a pluralistic society. The integration of religious moderation into the Islamic boarding school curriculum is regarded as a strategy for instilling inclusive Islamic values and preventing the development of extremist and intolerant attitudes.This study employed a qualitative approach using field research. Data were collected through observation, interviews, and documentation. The research informants consisted of the head of the Islamic boarding school, teachers, and students. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and method triangulation.The findings indicate that the internalization of religious moderation within the learning curriculum at Harisul Khairaat Bumi Hijrah Islamic Boarding School in Tidore is carried out by integrating the values of religious moderation into religious subjects and Islamic boarding school activities. The forms of internalization identified include the cultivation of tolerance (tasamuh), balance (tawazun), justice (i‘tidal), deliberation (shura), and exemplary conduct (qudwah). The internalization process occurs through three stages: value transformation, value transaction, and value transinternalization. Its implementation takes place through classroom learning, habituation in daily boarding school life, exemplary conduct demonstrated by teachers and caregivers, and various socio-religious activities involving the students. The findings demonstrate that this process contributes to the development of students who are moderate, tolerant, respectful of differences, and characterized by balanced and non-extremist religious attitudes. These findings are consistent with previous studies that position the Islamic boarding school curriculum as a strategic medium for strengthening religious moderation.